Design and Simulation of Appropriate Digital Watermarking Technique for Secure and Reliable Data Communication - Ashish Raj, Manoj Gupta, Sandeep Kumar Dayma (International Journal of Modern Agriculture, 2021)
The latest advancements in the field of multimedia promised significant improvements in data transit, transmission, and manipulation. Along with the expansion of facilities, there are greater dangers to data authentication, licenced use, and data security from unlawful usage. Copyright infringement, tampering, and unlawful distribution of digital media have all been presented as reasons for using digital watermarking (e.g. video, audio, and images). The watermark indicates whether or not the data has a copyright. The field of information concealment has exploded in popularity. However, numerous doubts remain about the technology’s potential and role in establishing and maintaining intellectual property rights in the digital age. This paper gives an overview of information concealment, highlighting its key disciplines (covert channels, stenography, digital watermarking, and anonymity) as well as some of the applications that are currently generating interest. The focus is on the state of digital watermarking and its prospects, with a taxonomy based on insertion domain, applicability, and types of existing methods receiving significant attention. This thesis presents a new technique for meeting the world’s digital watermarking demands by focusing on embedding watermarks in the R-G-B planes of colour images. The colour image is watermarked three times for intellectual property rights protection by embedding the same watermark in each plane of the multimedia image. Watermarks are put into individual colour planes when multimedia images are segmented into R-G-B colour planes. In one or more of the colour planes, one or more watermarks can be placed. The authentication procedure involves retrieving watermarks from all three-color planes and constructing a final watermark from the intersection of all the obtained watermarks. With existing approaches as well as a new proposed methodology, the suggested work has been implemented in both the spatial and transform domains. The threshold-based correlation watermarking approach is employed in the spatial domain, while DCT based watermarking and correlation based DCT watermarking are employed in the transform domain. Finally, the performance of digital watermarking systems is assessed as a tradeoff between message carrying capacity, attack robustness (e.g., Gaussian noise, JPEG compression), and embedding caused distortion. In comparison to existing methodologies, our proposed methodology has produced better outcomes.